(untitled) - Bird, Graham (New York, 2003)
There are many challenges facing the economies of developing countries. Capital volatility, financial crises, aid, debt and the IMF are all issues that have received a great deal of attention over recent years. In International Finance and the Developing Economies, Graham Bird provides an essentially non-technical discussion of these issues, examining the underlying political economy and discussing the policy alternatives that are available.
Keywords: International monetary fund,International finance,Finance,Structural adjustment (economic policy); Developing countries,Developing countries,Developing countries